The pursuit of happyness [videorecording (DVD)] - Muccino, Gabriele; Smith, Will, 1968-; Smith, Jaden, 1998-; Newton, Thandiwe, 1972- (Sony Pictures Home Entertainment, 2007)
In 1981, Chris Gardner was a struggling salesman. His wife worked double shifts to support the family including their young son, Christopher. In the face of this difficult life, Chris has the desperate inspiration to try for a stockbroker internship where one in twenty has a chance of a lucrative full time career. Even when his wife leaves him because of this choice, Chris clings to this dream. The odds become more daunting by the day. Together, father and son struggle through homelessness, jail time, tax seizure and the overall punishing despair in a quest that would make Gardner a respected millionaire.